Herbal Medicines: A Potent Approach to Human Diseases, Their Chief Compounds, Formulations, Present Status, and Future Aspects - Ghosh, Somnath; Bishal, Amlan; Ghosh, Shirsa Kumar; Jana, Koushik; Gayen, Bikash; Sahu, Suman; Debnath, Biplab (International Journal of Membrane Science and Technology, 2023)
Humans have relied on herbal medicines in health care and the treatment of numerous diseases since the very early stages of civilization. Herbal medicines or phytomedicines not only treat sickness but also guard against its complications simultaneously. The continuous use of synthetic medications is not safe for health because of their extreme negative impacts. So now a days, we can estimate that in some developing countries, such as the USA and England, herbal drugs make up to 25% of all consumption; on the other hand, in a few nations that are rapidly developing, like India and China, it comprises up to 80%. All over the world, more than ten thousand medicinal species are present. India is a well known producer of herbal plants that have a history of being used medicinally. As per the data of the International Union for Conservation of Nature (IUCN) and the World Wide Fund for Nature (WWF), there are 50000-80000 types of flowering plants that have medicinal value globally. Because they are less expensive, more acceptable in society and culture, better compatible with the human body, and cause less adverse effects, herbal medicines are currently in considerable need for primary healthcare in developing countries. Scientific understanding of plants advanced over the 19th and 20th centuries, and active chemicals that are utilized to create new medicines were isolated. However, there are other issues with using phytomedicines that need to be resolved. This time period also saw the rise of herbal pharmacopoeias, standardized herbal preparations, and larger-scale production of herbal medicines for the future development of not only this field but also for the 80% of the world's population that belongs to the extreme limit of poverty. This study attempts to review different potent approach of herbal medicines, their current status and their future aspects.